Inferring continental ancestry of argentineans from autosomal, y-chromosomal and mitochondrial dna - Corach, Daniel (2010)
We investigated the bio-geographic ancestry of Argentineans, and quantified their genetic admixture, analyzing 246 unrelated male individuals from eight provinces of three Argentinean regions using ancestry-sensitive DNA markers (ASDM) from autosomal, Y and mitochondrial chromosomes. Our results demonstrate that European, Native American and African ancestry components were detectable in the contemporary Argentineans, the amounts depending on the genetic system applied, exhibiting large inter-individual heterogeneity. Argentineans carried a large fraction of European genetic heritage in their Y-chromosomal (94.1%) and autosomal (78.5%) DNA, but their mitochondrial gene pool is mostly of Native American ancestry (53.7%); instead, African heritage was small in all three genetic systems (<4%). Population substructure in Argentina considering the eight sampled provinces was very small based on autosomal (0.92% of total variation was between provincial groups, p = 0.005) and mtDNA (1.77%, p = 0.005) data (none with NRY data), and all three genetic systems revealed no substructure when clustering the provinces into the three geographic regions to which they belong. The complex genetic ancestry picture detected in Argentineans underscores the need to apply ASDM from all three genetic systems to infer geographic origins and genetic admixture. This applies to all worldwide areas where people with different continental ancestry live geographically close together.